2018
DOI: 10.3389/fphys.2018.00526
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Cholesterol Transport: Molecular Mechanisms and the Non-medical Approach to Enhance HDL Cholesterol

Abstract: Dyslipidemia (high concentrations of LDL-c and low concentrations of HDL-c) is a major cause of cardiovascular events, which are the leading cause of death in the world. On the other hand, nutrition and regular exercise can be an interesting strategy to modulate lipid profile, acting as prevention or treatment, inhibiting the risk of diseases due to its anti-inflammatory and anti-atherogenic characteristics. Additionally, the possibility of controlling different training variables, such as type, intensity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
80
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 82 publications
(91 reference statements)
0
80
0
1
Order By: Relevance
“…RCT is the major route for removal of excess cholesterol from peripheral tissues and its transport to the liver, by which HDL protects against atherosclerotic cardiovascular disease [37]. In RCT, excess cholesterol from macrophage foam cells is transferred and carried by HDL to the liver for excretion as bile acids or free cholesterol into the feces, including ApoA1-activated LCAT-mediated HDL maturation, HDL cholesterol uptake via SR-BI, and biliary cholesterol secretion by ABCG5 and ABCG8 [38]. Our results showed an increased hepatic expression of SR-B1, ABCG5, ABCG8, LCAT, and ApoA1 in L. plantarum treated mice (Fig 2H), from which it is indicated that L. plantarum treatment contributes to prevent elevated cholesterol levels by promoting RCT.…”
Section: Discussionmentioning
confidence: 99%
“…RCT is the major route for removal of excess cholesterol from peripheral tissues and its transport to the liver, by which HDL protects against atherosclerotic cardiovascular disease [37]. In RCT, excess cholesterol from macrophage foam cells is transferred and carried by HDL to the liver for excretion as bile acids or free cholesterol into the feces, including ApoA1-activated LCAT-mediated HDL maturation, HDL cholesterol uptake via SR-BI, and biliary cholesterol secretion by ABCG5 and ABCG8 [38]. Our results showed an increased hepatic expression of SR-B1, ABCG5, ABCG8, LCAT, and ApoA1 in L. plantarum treated mice (Fig 2H), from which it is indicated that L. plantarum treatment contributes to prevent elevated cholesterol levels by promoting RCT.…”
Section: Discussionmentioning
confidence: 99%
“…training, especially at moderate intensity protocols, is associated with the regulation of the lipid profile, decreasing concentrations of total cholesterol, LDL-c, triacylglycerol, and increasing HDL-c, being this process facilitated by reverse cholesterol transport mediated by enzymatic modulation of lecithin-cholesterol acyltransferase (L-CAT) and cholesteryl ester transfer protein (CETP) 9 .…”
mentioning
confidence: 99%
“…The indirect impact of the intervention on adiposity via HDL/cholesterol might be due to the positive relationship between aerobic capacity and lipid profile regulation. This relationship is associated with the enzymatic modulation of lecithin‐cholesterol acyltransferase (L‐CAT), which is involved in the esterification of cholesterol 27 . In addition, cholesteryl ester transfer protein (CETP) is one of the facilitators of the transport of cholesterol ester particles of HDL‐c to other lipoproteins, 28,29 since both L‐CAT and CETP are part of the mechanism in which the excess of cholesterol is removed from the peripheral tissues and both pathways are stimulated by physical activity 27 .…”
Section: Discussionmentioning
confidence: 99%
“…This relationship is associated with the enzymatic modulation of lecithin‐cholesterol acyltransferase (L‐CAT), which is involved in the esterification of cholesterol 27 . In addition, cholesteryl ester transfer protein (CETP) is one of the facilitators of the transport of cholesterol ester particles of HDL‐c to other lipoproteins, 28,29 since both L‐CAT and CETP are part of the mechanism in which the excess of cholesterol is removed from the peripheral tissues and both pathways are stimulated by physical activity 27 . Moreover, aerobic exercise has been shown to activate the hydrolysis of the triacylglycerols (TAG) from very low‐density lipoprotein (VLDL) by lipoprotein lipase (LPL), which partly results, in the production of beneficial HDL‐c particles 30,31 .…”
Section: Discussionmentioning
confidence: 99%